Application of 3D Digital Image Processing Technology in Modern Packaging Design. (21st September 2022) - Meng, Kun; Liu, Fulong
Abstract : In this paper, a modern packaging model is constructed by combining three-dimensional digital image processing technology, which has achieved the effect of improving the quality of modern packaging design. In addition, this paper proposes a new target recognition and tracking scheme, which uses the method of servo motor to control the synchronous conveyor belt to monitor the moving objects in real time and proposes a decision analysis algorithm to avoid repeated identification of multiple moving targets. At the same time, the software structure and execution flow of the visual control system are designed, the level of each functional module of the software is divided, and the key technology of the software is studied. The experimental research shows that the 3D digital image processing technology is effective in improving modern packaging design methods and can improve the interactivity and user experience of modern packaging design.